(NpRASLAWQNSKIJ QZYK (B:s (NdOSTIVENIQ I PROBLEMY W EGO REKONSTRUKCII (B: (NpEREWOD S ANGLIJSKOGO (B/s - (NbIRNBAUM(B, (NhENRIKs; (NdYBO(B, (Nw(B.(Na(B.s; (NvURAWLEW(B, (Nw(B.(Nk(B.s ((NmOSKWA (B:s (NpROGRESS(B,s, 1987)
(NbIBLIOGR(B.: (NS(B. 345-452s
Keywords: (NpRASLAWQNSKIJ QZYKs